2018
DOI: 10.3390/ijms19051425
|View full text |Cite
|
Sign up to set email alerts
|

An aPPARent Functional Consequence in Skeletal Muscle Physiology via Peroxisome Proliferator-Activated Receptors

Abstract: Skeletal muscle comprises 30–40% of the total body mass and plays a central role in energy homeostasis in the body. The deregulation of energy homeostasis is a common underlying characteristic of metabolic syndrome. Over the past decades, peroxisome proliferator-activated receptors (PPARs) have been shown to play critical regulatory roles in skeletal muscle. The three family members of PPAR have overlapping roles that contribute to the myriad of processes in skeletal muscle. This review aims to provide an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 221 publications
2
58
0
Order By: Relevance
“…Thiazolidinediones target PPAR-γ. PPAR-γ are ligand activated transcription factors and activation of PPAR-γ results in insulin sensitization and increases glucose metabolism [181,182]. Thiazolidinediones work by making the adipocytes, liver and muscle cells more sensitive to insulin and by conserving the β-cell function.…”
Section: Treatment Of Pre-diabetesmentioning
confidence: 99%
“…Thiazolidinediones target PPAR-γ. PPAR-γ are ligand activated transcription factors and activation of PPAR-γ results in insulin sensitization and increases glucose metabolism [181,182]. Thiazolidinediones work by making the adipocytes, liver and muscle cells more sensitive to insulin and by conserving the β-cell function.…”
Section: Treatment Of Pre-diabetesmentioning
confidence: 99%
“…A considerable number of studies have also found that metformin decreases fasting plasma glucose (PG) concentration and hemoglobin A1c by conserving the β-cell function or by decreasing liver glucose production (hepatic gluconeogenesis) (181)(182)(183)(184). Also, thiazolidinediones can promote insulin sensitivity, increase glucose metabolism, and preserve the β-cell function through activating PPAR-γ (185,186). Meanwhile, they can reduce plasma free fatty acid and intramyocellular lipid content to increase insulin sensitivity and redistribute fats from visceral to subcutaneous adipose to alleviate diabetes.…”
Section: Pharmacological Intervention For Sarcopenic Obesity and Diabmentioning
confidence: 99%
“…Since fatty acids and their derivatives are agonists of PPARs [31], we asked if FoxA2 expression could be regulated by PPARβ/δ, the predominant PPAR isotype in skeletal muscle [13]. GW501516 (GW), a highly selective PPARβ/δ agonist, increased the mRNA and protein levels of FoxA2 in C2C12 myotubes in a dose-and time-dependent manner ( Figure 3A,B).…”
Section: Pparβ/δ Upregulates Foxa2 Expression In C2c12 Cellsmentioning
confidence: 99%
“…They are activated by endogenous ligands, such as free fatty acids and their derivatives, and by a variety of synthetic drugs used in the treatment of metabolic syndrome and type 2 diabetes [10,11]. PPARβ/δ is the predominant isotype in skeletal muscle and its activation increases lipid uptake and catabolism via β-oxidation [12], along with a shift towards oxidative fibers, which enhances oxidative capacity and promotes running endurance, leading to an overall reduction in body fat [13][14][15]. Conversely, selective PPARβ/δ ablation in skeletal muscle leads to lower oxidative capacity in the fibers, resulting in obesity and diabetes [16].…”
Section: Introductionmentioning
confidence: 99%